Flexible deep-ultraviolet light-emitting diodes for significant improvement of quantum efficiencies by external bending. (16th February 2018) - Shervin, Shahab; Oh, Seung Kyu; Park, Hyun Jung; Lee, Keon-Hwa; Asadirad, Mojtaba; Kim, Seung-Hwan; Kim, Jeomoh; Pouladi, Sara; Lee, Sung-Nam; Li, Xiaohang; Kwak, Joon Seop; Ryou, Jae-Hyun
Abstract: We report a new route to improve quantum efficiencies of AlGaN-based deep-ultraviolet light-emitting diodes (DUV LEDs) using mechanical flexibility of recently developed bendable thin-film structures. Numerical studies show that electronic band structures of AlGaN heterostructures and resulting optical and electrical characteristics of the devices can be significantly modified by external bending through active control of piezoelectric polarization. Internal quantum efficiency is enhanced higher than three times, when the DUV LEDs are moderately bent with concave curvatures. Furthermore, an efficiency droop at high injection currents is mitigated and turn-on voltage of diodes decreases with the same bending condition. The concept of bendable DUV LEDs with a controlled external strain can provide a new path for high-output-power and high-efficiency devices.